Ultrasonic Lamb Wave Detection Based on a Tunable, Narrow-Linewidth, and Frequency-Locked Fiber Laser - Jingjing Guo; Changxi Yang (IEEE Photonics Journal, 2017)
Developments of advanced ultrasonic sensors have made significant impact in structural health monitoring as well as in other various fields including electronics, biomedicine, and geophysics. We describe a cost-effective, highly stabilized, and sensitive ultrasonic sensing system based on a tunable, narrow-linewidth fiber laser locked to resonance of a phase-shifted fiber Bragg grating (PS-FBG). Stable single-longitudinal-mode (SLM) operation of the fiber laser is achieved with a narrow-band self-written FBG that dynamically tracks the lasing wavelength. The SLM fiber laser with 1.48-kHz linewidth and 40-nm tuning range is frequency locked to the PS-FBG resonance in Pound–Drever–Hall configuration for robust and sensitive ultrasonic detection. The sensing system exhibits a high signal-to-noise ratio for ultrasonic detection and further application of the system for lamb wave detection makes it especially attractive for structural health monitoring.